Exploring the attitudes and beliefs of Saudi female nursing students towards sexual healthcare: mixed method study - Almegewly, Wafa; Hussein, Rasha Mohammed; Khedr, Mahmoud Abdelwahab (Frontiers in Public Health, 2025)
ObjectivesThis study aims to explore the attitudes and beliefs of Saudi female nursing students towards sexual healthcare.MethodsA mixed-methods research design was employed on a sample of 247 Saudi female undergraduate nursing students using a non-probability sampling technique that incorporated a combination of purposive and snowball sampling. The participants completed an online questionnaire covering sociodemographic characteristics and the Sexual Attitudes and Beliefs Scale (SABS), two open-ended questions asking about the reasons for denying sexual healthcare and related issues.ResultsThe study found that nursing students had a poor attitude towards discussing sexuality as essential to patients’ health outcomes, with a mean score of 2.3 (SD = 1.4). Correlational analyses revealed a significantly high positive correlation between age and year of the program (r = 0.828, p < 0.001), a significant but very low positive association between age and Grade Point Average (GPA) (r = 0.198, p = 0.046), and a significant negative correlation between the belief that “discussing sexuality is essential to patients’ health outcomes” and nursing students’ GPA (r = −0.173, p = 0.006).ConclusionThe exploration of Saudi female nursing students’ attitudes and beliefs towards sexual healthcare reveals a nuanced landscape where attitudes vary across different aspects of sexual health discussions.